Determinan Perilaku Disfungsional Auditor: Peran Emotional Spiritual Quotient Sebagai Variabel Moderasi - Denny Setiawan; Muhammad Irfan Tarmizi (Politeknik Ganesha Medan, 2026)
The purpose of this study is to examine the influence of reward and punishment, audit fees, and time budget pressure on dysfunctional auditor behavior, with Emotional Spiritual Quotient (ESQ) serving as a moderating variable. This study contributes to the behavioral auditing literature in clarifying determinants that shape auditor conduct and professional judgment in audit engagements. The population comprises auditors employed at Public Accounting Firms (KAP) in Banten Province. A purposive sampling technique was applied, initially targeting 28 KAPs to ensure adequate representation. However, due to limited cooperation from several firms in providing official responses and returning questionnaires within the predetermined timeframe, only 15 KAPs were included, resulting in 107 usable responses. Data were analyzed using Moderated Regression Analysis (MRA) with IBM SPSS Statistics 27 to ensure systematic and reliable findings. The results indicate that reward and punishment mechanisms, along with audit fees, have a significant negative effect on dysfunctional auditor behavior, emphasizing the importance of appropriate incentives in fostering ethical conduct. In contrast, time budget pressure exhibits a significant positive effect, suggesting that excessive workload pressure may increase the likelihood of dysfunctional practices. Although ESQ demonstrates a direct negative influence, moderation testing reveals that ESQ does not weaken the relationships between the independent variables and dysfunctional auditor behavior. Overall, effective compensation systems and time management are essential for maintaining auditor integrity.